Comparison between girls and boys lifestyle profile and physical activity - Tozo, Tatiana Affornali (2021)
The aim of this study was to compare lifestyle profile and physical activity between girls and boys. A total of 336 students 11 to 17 years old participated in the study (51.5% female). Height, body mass, sexual maturation and z-score body mass index (BMI-z) were assessed. The level of physical activity (PA) was determined through the International Physical Activity Questionnaire (IPAQ). Lifestyle was assessed using the Individual Lifestyle Profile questionnaire (PEVI), computing the total scores from five components and considering the following cutoff points: >30 points = favorable PEVI; and ≤30 points = unfavorable PEVI. Results showed 35.1% of the students were considered overweight, 74.78% did not comply with the recommendations for physical activity and 31.5% presented unfa-vorable PEVI. There was a difference between boys and girls in moderate to vigorous physical activity (MVPA) (p = 0.048). Boys presented better lifestyle (p = 0.06) and had, on average, more light PA (p < 0.01), moderate PA (p < 0.01), vigorous PA (p < 0.01) and MVPA (p < 0.01) than girls. Girls with favorable PEVI had higher average levels of light PA than those with unfavorable PEVI (p < 0.001). It was concluded that boys are more active during the week when compared to girls. However, they also present fewer concerns with preventive behaviors and relationships. Light PA was higher in girls with a favorable lifestyle profile.